HÉRNIA UMBILICAL EM BEZERRO: RELATO DE CASO - Lenhart, Daniel de Souza; Dal Chiavon, Gessica Jaíne; Parise, Sabrina; Daneluz, Marina Oliveira; Carneiro, Maico Fernando Wilges; Ansilieiro, Willian Jonas (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.